Mediasi Motivasi Kerja Pada Pengaruh Kepemimpinan Kewirausahaan dan Budaya Organisasi Terhadap Produktivitas Kerja CV Mandala Utama - Enjang Suherman; suroso (Universitas Serang Raya, 2022)
Some research were done to determine several factors that cause low work productivity. One of them is leadership, but there are inconsistencies in the influence of leadership on productivity. Therefore, an intermediate variable that links leadership with productivity is needed, namely work motivation. Besides, organizational culture can affect productivity through work motivation. Effective leadership at this time is leadership that has entrepreneurial characteristics. Thus, the purpose of this study will be to examine the significance of work motivation as a mediator on entrepreneurial leadership and organizational culture on work productivity. This research method is descriptive verification that examines causality between variables using SMART PLS-SEM analysis. The population of this study is 132 employees and a sample of 99. The results of the study state that entrepreneurial leadership is quite good, organizational culture is quite strong, work motivation and work productivity are high enough. Entrepreneurial leadership and organizational culture partially have a significant effect on work motivation. work motivation significantly affects work productivity, and work motivation mediates entrepreneurial leadership and organizational culture affects work productivity. Keywords: Entrepreneurial Leadership, Organizational Culture, Work Motivation, Productivity.